Analysis of User Experience and Cognitive Psychology Approaches to the Convenience of KRS-Online Information System Users as Material for System Evaluation and Development - Kurnia Manggali Utamaningrum; Wahyu Andhyka; Evi Dwi Wahyuni (Universitas Muhammadiyah Sidoarjo, 2017)
The implementation of the academic information services, UMM has been trying to present some system of academic services for the various students needs, one of the highlights is KRS-Online system because it is the most frequently used system of students in programming courses in each semester.Complaints and suggestions certainly are reasonable for the system services are used by many people.This study aimed to KRS-Online users’ convenience can be measured empirically based indicators of variable users’ experience and cognitive psychology to prove whether these two variables can affect the users’ convenience.Based on this research, it has been proved that the users’ experience and cognitive psychology significantly affect both users’ convenience variables partially tested individually or simultaneously or together.